2016
DOI: 10.1016/j.otsr.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Prospective observational study of midtarsal joint sprain: Epidemiological and ultrasonographic analysis

Abstract: MJS is frequent, difficult to diagnose clinically, and often severe. Clinical presentation and injury mechanisms differ from ankle sprain. Ultrasound seems to be an indispensable tool in diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 14 publications
0
20
0
1
Order By: Relevance
“…However, little has been reported on subtalar, midtarsal and tarsometatarsal joint injuries associated with foot and ankle sprain. ( 12 , 13 ) Thus, injuries of these structures are commonly neglected or underdiagnosed and are usually managed with an empiric, non-specific and ineffective approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little has been reported on subtalar, midtarsal and tarsometatarsal joint injuries associated with foot and ankle sprain. ( 12 , 13 ) Thus, injuries of these structures are commonly neglected or underdiagnosed and are usually managed with an empiric, non-specific and ineffective approach.…”
Section: Introductionmentioning
confidence: 99%
“…Porém, pouco tem sido relatado em relação às lesões da articulação subtalar, mediotársica e tarsometatársicas na ocorrência de entorses do pé e tornozelo. ( 12 , 13 ) Assim, as lesões destas partes são comumente negligenciadas ou subdiagnosticadas, sendo costumeiramente manejadas de maneira empírica, inespecífica e pouco efetiva.…”
Section: Introductionunclassified
“…The midtarsal joint, also known as the transverse tarsal joint or Chopart's joint, comprises the talonavicular joint medially and the calcaneocuboid joint laterally. 3 It is stabilised by the talonavicular, bifurcated and dorsal and plantar calcaneocuboid ligaments (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…1 They are hard to diagnose clinically 2 and poor diagnostic recognition may lead to painful sequelae in the absence of appropriate treatment. 3 This case report presents a patient with a history of ankle trauma where ultrasound recognition of midtarsal joint changes resulted in diagnostic recognition of a midtarsal joint sprain.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] These are the same mechanisms that produce a sprain of the anterior talofibular ligament of the ankle, which has been termed a sprainfracture. An epidemiological observational study of midtarsal joint sprain showed that the most frequent trauma mechanism was foot inversion (76% of cases), followed by plantar hyperflexion (21%), dorsal hyperflexion (2%), and foot eversion (1%) [ 6 , 18 , 21 – 24 ] (Fig. 5 ).…”
Section: Discussionmentioning
confidence: 99%